Meaningful connection in virtual classrooms: graduate students’ perspectives on effective instructor presence in blended courses - McNeill, Laura; Bushaala, Saad (Frontiers in Education, 2023)
This qualitative study explored 15 graduate students’ perspectives on effective online instructor presence. Analysis of interviews, a survey, and a focus group revealed students value early relationship-building through consistent participation, authentic personality-sharing, and learner-centered course design. Results indicate effective instructor presence fosters trust, satisfaction, engagement, and positive student mindsets while reducing stress and anxiety. Students preferred visible, accessible instructors who connect through prompt communication, constructive feedback, and active listening. Additional findings suggest leveraging synchronous interactions enhances social presence and relationship-building. However, disconnected instructor presence caused frustration and negative emotions. Overall, intentional instructor presence is critical for successful online instruction and profoundly shapes learners’ holistic experiences beyond solely academic goals. While limited to one program, these learner-centered insights provide a starting point for identifying high-impact presence-building strategies tailored to graduate contexts.